Maqasid al-Shari'ah and Contemporary Reality: Three Theses on the Approach - Ghanem, إبراهيم البيومي (Journal of Contemporary Maqasid Studies, 2023)
The current study aims to identify effective ways for the maqasid theory by linking it with reality, for it has encountered several methodological defects at the scientific and practical levels. The study presented three theses to renew the approach of the subject of maqasid (purposes). The first thesis is that the system of maqasid should be restructured, by indicating common and general purposes such as achieving human dignity, and freedom, applying justice, and achieving public harmony and peace. The second thesis is to expand the sources of research on the subject of maqasid, as the paper shows a set of methodological imbalances and defects, which made the system of “general purposes of Shari’ah” more theoretical and does not achieve its desired practical objectives. The third thesis is the need to update and renew explanatory examples because illustrations are one of the tools to liberate the maqasid theory from its restraints. Therefore, the study calls for using relevant examples with actual reality, especially on matters related to collective reality and common interests.